Plant diversity on high elevation islands – drivers of species richness and endemism - Severin D.H. Irl (Frontiers of Biogeography)
High elevation islands elicit fascination because of their large array of endemic species and strong environmental gradients. First, I define a high elevation island according to geographic and environmental characteristics. Then, within this high elevation island framework, I address local disturbance effects on plant distribution, drivers of diversity and endemism on the island scale, and global patterns of treeline elevation and climate change. Locally, introduced herbivores have strong negative effects on the summit scrub of my model island La Palma (Canary Islands), while roads have unexpected positive effects on endemics. On the island scale, topography and climate drive diversity and endemism. Hotspots of endemicity are found in summit regions – a general pattern on high elevation islands. The global pattern of treeline elevation behaves quite differently on islands than on the mainland. A thorough literature review and climate projections suggest that climate change will profoundly affect oceanic island floras.